Does Tourism Development Influence the Economic Growth in Pakistan? Evidence from ARDL and Causality Approach - Iqbal, Mujahid; Khawer, Aminah; Khan, Ghulam Sajjad; Irshad, Muhammad Saqib (iRASD Journal of Economics, 2024)
This study analyzes the influence of tourism development on economic growth (GDP) in the case of Pakistan’s economy using the time series data covering the spanning from 1995-2022. In order to unveil reliable and robust results, a more appropriate time-series approach was applied for the current article. Time series unit root tests infer that all the variables have unit root problems at levels I(0), however, after taking the first difference I(1), all series turn into following the stationary process. Furthermore, (ARDL) bound test reveals that a long-term cointegration prevails among all analyzed variables. The Granger causality test is also utilized to check the causal relationship among the series. The long-run elasticity estimates examine a statistically significant and positive link between the sect tourism sector GDP growth in the case of Pakistan. Furthermore, political instability and inflation rate have an inverse influence on GDP growth, whereas, capital investment has a positively significant influence on GDP growth. In addition, it is concluded that tourism sector development helps to move upward shift in the economy of Pakistan by generating more profits for the country. Finally, it is suggested that goverment should have to focus on investing in the tourism sector and provide better facilities for tourists.